2014
DOI: 10.1038/modpathol.2013.216
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ARID1A expression and its relationship with PI3K-Akt pathway alterations and ZNF217 amplification in ovarian clear cell carcinoma

Abstract: AT-rich interactive domain 1A (ARID1A) is a subunit of switch/sucrose non-fermentable (SWI/SNF) complex. Recently, alterations of ARID1A gene, phosphatidylinositol 3-kinase-protein kinase B (PI3K-Akt) pathway and zinc-finger protein 217 (ZNF217) gene have been identified as frequent molecular genetic changes in ovarian clear cell carcinoma. The relationships between these events have not been studied and integrated in the same cohort. This study was aimed at determining the correlation between these molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 34 publications
(54 reference statements)
5
69
0
Order By: Relevance
“…In previous studies, molecular alterations in ovarian clear cell carcinomas, including ARID1A, PIK3CA, and ZNF217, were either not considered a prognostic factor or signified different conclusions. 22,24,[32][33][34][35][36][37] Our study is the first report on the prognostic impact of TERT promoter mutations in early-stage ovarian clear cell carcinomas. TERT promoter mutations may have a role in the development of chemoresistance, but more in-depth investigations are necessary.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In previous studies, molecular alterations in ovarian clear cell carcinomas, including ARID1A, PIK3CA, and ZNF217, were either not considered a prognostic factor or signified different conclusions. 22,24,[32][33][34][35][36][37] Our study is the first report on the prognostic impact of TERT promoter mutations in early-stage ovarian clear cell carcinomas. TERT promoter mutations may have a role in the development of chemoresistance, but more in-depth investigations are necessary.…”
Section: Discussionmentioning
confidence: 69%
“…Some cases of ovarian clear cell carcinoma were also reported in our previous study. 22 All patients underwent operations including total hysterectomy with bilateral salpingo-oophorectomy, at least, and no concurrent endometrial and ovarian clear cell carcinomas were found. All patients with ovarian clear cell carcinoma underwent debulking surgery.…”
Section: Patients and Tissue Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrate that an ARID1A deficit has those three effects on tumor suppression (21). An ARID1A deficit has also been associated with the activation of the phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) signaling pathway, and with the amplification of zinc-finger protein 217 (ZNF217), which are involved in cancer development (24).…”
Section: Chromatin Remodeling-associated Gene Mutations and Carcinogementioning
confidence: 84%
“…Firstly, we identified potential targetable genomic mutations in CCC using an extensive literature search (24,25). Patients with CCC (64%) had ≥1 somatic mutation (24).…”
Section: Candidate Mutated Genes For Enhancing the Therapeutic Ratio mentioning
confidence: 99%